Tinjauan Kriminologis Terhadap Tindakan Penikaman Yang Terjadi Di Kelurahan Fatululi Kecamatan Oebobo Kota Kupang - BEDA PAUKUMA, ZAINUDDIN MUHAMMAD ZIDANE; Kadja, Thelma S.M; Kian, Darius A. (Law Faculty, Nusa Cendana University, 2023)
Stabbing is a criminal act that wants to eliminate someone's life, currently there are many stabbing cases in various regions of Indonesia. The occurrence of stabbings in Indonesia varies greatly, this is influenced by the moral decline of this nation. In 2021 there was a case with case number 115/Pid.B/2021/PN Kpg of persecution on Sunday, April 25th in Kupang City, an act of stabbing was committed by Melkianus saku (MS) aged 43 years to Theodorus suni (TS) aged 40 years. The main problems in this thesis are: (1) What are the factors that cause the occurrence of acts of stabbing that occurred in Fatululi Village, Oebobo District, Kupang City? (2) What are the countermeasures against acts of stabbing that occurred in Fatululi Village, Oebobo District, Kupang City? This research is an empirical legal research conducted in Kupang. Data collection techniques using interview techniques and library research and field research. The data used are primary and secondary data. This research was conducted at the Kupang City Resort Police. The results of data processing were analyzed descriptively qualitative. Based on the results of research and discussion, it can be seen: (1) the factors that cause the stabbing that occurred in Fatululi Village, Oebobo District, Kupang City are internal factors. (2) Countermeasures against acts of stabbing that occurred in Fatululi Village, Oebobo District, Kupang City are pre-emtif efforts, preventive efforts and repressive efforts.